Exploring the neuroprotective activity of a lignanamides-rich extract in human neuroblastoma SH-SY5Y cells under dimethyl sulfoxide-induced stress - Mallardo, Marta; Pacifico, Severina; Piccolella, Simona; Di Meo, Irene; Rizzo, Maria Rosaria; Daniele, Aurora; Nigro, Ersilia (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Dimethyl sulfoxide (DMSO) is widely used as a diluent and/or solvent for pharmacological compounds. Furthermore, DMSO crosses the blood-brain barrier acting on the nervous system. The natural compounds phenylamides and lignanamides (LnHS) have protective effects on neuronal health, being promising neuroprotective candidates. In this scenario, we evaluated the impact of DMSO and/or LnHS on SH-SY5Y and U-87 cells, taken as in vitro model of neurons and glia. Methods: Cells were treated with DMSO and/or LnHS at different doses and proliferation (MTT and trypan blue counting, colony forming ability, autophagy, oxidative stress (NO, ROS determination) and inflammatory (IL8, IL6, TNFα mRNA expression) response was evaluated. Results: We found that DMSO reduces both neuronal and glial cell viability, while LnHS does not affect viability of SH-SY5Y cells but reduces that of U-87 cells. Therefore, we focused on SHSY5Y cells and investigated whether LnHS could counteract DMSO toxicity. LnHS partially attenuates the inhibitory effects of DMSO on cell viability and restores the colony-forming ability of SH-SY5Y cells exposed to DMSO. Furthermore, we found that co-administration of LnHS modulates the expression of SIRT3 and SOD2 enzymes, reduces nitrite release and ROS generation increasing IL-8 levels. Interestingly, co-administration of LnHS counteracts the DMSO-induced production of IL-6, while no modification in TNF-α was found. Discussion: Our study indicates LnHS as a potential feasible compound to support neuronal health as it counteracts DMSO induced cytotoxic effects by improving SH-SY5Y cells survival. Further studies are needed to clarify the molecular mechanisms underlying the LnHS biological activities.